Comparison of effect of eutectic mixture of local anesthetics, amethocaine and 4% lignocaine in alleviating pain during venous cannulation in children up to three years - Sharma, Rakesh; Kumar, Pancham; Sood, Ambika; Gupta, Satendra (International Journal of Contemporary Pediatrics, 2022)
Background: Intense anxiety experienced by the parents and their children regarding venous cannulation may result in non-adherence to the recommended procedure. The aim of present study was to compare the effects of eutectic mixture of topical anesthetics, amethocaine and 4% lignocaine on pain responses during venous cannulation in children up to 3 years. Methods: The present hospital based, prospective, randomized comparative study was conducted from December 2019 to November 2020 at KNH and IGMC, Shimla. The study population was divided in to two groups, group I (less than one month) and group II (one month to three years) and were further divided into three groups (amethocaine, EMLA and 4% lignocaine). NIPS and FLACC score for 3 events (pre procedural, immediately after cannulation and three minutes after cannulation) were noted. Results: 99 children were enrolled in our study (59 in group one and 40 in group two) and all were fulfilling inclusion criteria. NIPS score was highest for lignocaine before, immediate and after cannula followed by EMLA and was least for amethocaine. FLACC score was highest for lignocaine before, immediate and after cannulation. FLACC score was lowest for amethocaine, immediately and after cannulation and for EMLA before cannulation. Conclusions: Amethocaine significantly reduces the pain response as compared to EMLA and 4% lignocaine group specifically immediately after cannulation and three minutes post cannulation.